2021
DOI: 10.1080/17518253.2021.1963492
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant, anti-glycation and toxicity studies on silver nanoparticles synthesized using Rosa damascena flower extract

Abstract: The perspective of this research was to investigate the antioxidant, antibacterial, cytotoxic activity and anti-glycation of the SNPs synthesized by aqueous flower extract of pink Rosa damascena plant and compare with the biological effect of plant extract. The antioxidant activity of plant extract, and SNPs, their inhibitory effect on albumin glycosylation and also the cytotoxic effect on the human fibroblast cells were assessed by DPPH, spectrophotometric assay and MTT test, respectively. The antibacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…According to these results, Ag NPs would be the main inhibitor of bacterial growth both in the presence and absence of Cu NPs. The antibacterial activity of Ag NPs is widely known, and the inhibition concentration can vary depending on the physicochemical properties of NPs. However, the NP concentration range used in this study did not allow us to evaluate the minimum NP concentration that would determine the antibacterial activity difference between bimetallic NPs and Ag NPs.…”
Section: Resultsmentioning
confidence: 99%
“…According to these results, Ag NPs would be the main inhibitor of bacterial growth both in the presence and absence of Cu NPs. The antibacterial activity of Ag NPs is widely known, and the inhibition concentration can vary depending on the physicochemical properties of NPs. However, the NP concentration range used in this study did not allow us to evaluate the minimum NP concentration that would determine the antibacterial activity difference between bimetallic NPs and Ag NPs.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the plant-mediated Fe 2 O 3 NPs were very essential on inhibiting the growth of AGE products . Similarly, Peron and colleagues synthesized silver nanoparticles from the pink Rosa damascena plant and have used them to minimize the effects of glucose levels and prevent the production of AGE products . A recent study reports that flavones exhibit stronger inhibitory effects on AGE products with respect to flavanones, flavonols, and isoflavones …”
Section: Resultsmentioning
confidence: 99%
“…Aminoguanidine was included as the control group. The relative quantity of glycated BSA-glucose was identified by using the emission and excitation wavelengths of spectrophotometry …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both necrosis and vacuolar degeneration were dramatically increased in the AL group, which again was in line with other findings. However, RDA 1000 was significantly successful in lowering the damage in the mentioned aspects, which is likely due to its high protectivity characteristics by regulating the antioxidant system [ 61 , 62 ], reducing the ROS [ 63 , 64 ], and simultaneously increasing the antioxidant capacity of the body [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%